نماذج من التفسيرات الفقهية للإمام ابن نجيم من خلال كتابه " البحر الرائق شرح كنز الدقائق ":دراسة وصفية تحليلية: Examples of Jurisprudential Interpretations of Imam Ibn Nujaim through his book "Al-Bahr al-Rā’iq” Explanation of “Kanz al-Daqā’iq": Descriptive Analytical Study (Al-Qamar, 2022)
One of the best legal science is to engage in the words of Allah revealed to Hazrat Muhammad in clarifying, explaining its meaning ruling significances and words. This science is called the science of interpretation. The interpreter's approaches varied in interpreting the holy Quran, some of them follow the common methodology such as Mathur, Language and opinions such as al-Tebari. There is no doubt that the jurisprudence interpretation of the holy Quran has a great value, so sharia scholars has divided the topics of the holy Quran in three categories. The first section is related to the belief in monotheism, or religion the second section is related to the morals and the third one deals with the practical provisions and these provisions are extracted from the holy Quran this is called the jurisprudence of Quran or the provisions of the Quran. A person can not become a complete Muslim with out knowing this because people need them in their worships, dealings and activities of the life. Looking at this importance, scholars before and after studied these verses under a specific manner they called it"Ahkam ul Quran" Among the scholars, Allah chose a scholar named zainuddin ibni nujaim to serve his glorious book, in fact he was a great jurist. He was born in the city of Qahira in the year 926 Hijra. He was a model for the jurists, an Imam in matters of religion. That great scholar and personality died on Wednesday corresponding to the 8th Rajab in the year 970 Hijra.
Keywords: Ibn Nujaim; "Al-Bahr al-Rā’iq”; Explanation; “Kanz al-Daqā’iq; Study